The role of (18)F-FCH PET/CT in patients with uremic hyperparathyroidism compared with (99m)Tc-sestaMIBI SPECT/CT and ultrasonography - Xue, Yu (EJNMMI Res, 2019)
BACKGROUND: The aim of this study was to evaluate the diagnostic efficacy of (18)F-fluorocholine ((18)F-FCH) PET/CT for uremic hyperparathyroidism (uHPT) compared to (99m)Tc-sestaMIBI SPECT/CT and ultrasonography (US). METHODS: A total of 17 uHPT patients with stage 5 chronic kidney disease (CKD) were prospectively enrolled. All patients underwent US, (99m)Tc-sestaMIBI SPECT/CT, and (18)F-FCH within 2 months and received surgical treatment. Visual and quantitative methods were used for image analyses. Intraoperative localization and postoperative histological results of the reference standard as well as the sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of the three modalities were analyzed using Pearson’s χ(2) tests. In addition, the diagnostic efficacy of (18)F-FCH PET/CT for uHPT was evaluated. The relationships between PET parameters and laboratory parameters were assessed using the Spearman correlation coefficient. RESULTS: A total of 63 parathyroid hyperplasia lesions were resected in 17 uHPT patients, and 53 lesions were detected using (18)F-FCH PET/CT with no false-positive results. The sensitivity, specificity, accuracy, PPV, and NPV were 84.13%, 100%, 86.49%, 100%, and 52.38%, respectively. In comparison, the corresponding values for (99m)Tc-sestaMIBI SPECT/CT and US were 63.49%, 90.91%, 67.57%, 97.56%, and 30.30% and 61.90%, 81.82%, 64.86%, 95.12%, and 27.27%, respectively. The volume of hyper-functioning parathyroid glands was significantly different between lesions positive in (18)F-FCH PET/CT and negative in (18)F-FCH PET/CT (mean volume 1.36 ± 0.55 cm(3) vs. 0.83 ± 0.26 cm(3); P = 0.019). US misidentified intrathyroidal parathyroid hyperplasia as thyroid nodules in three patients, while (18)F-FCH PET correctly identified the anatomy. No significant associations were observed between PET parameters and laboratory parameters in uHPT. CONCLUSION: (18)F-FCH PET/CT was more sensitive and accurate for uHPT than (99m)Tc-sestaMIBI SPECT/CT and US, and had better preoperative diagnostic efficacy, particularly for lesions diagnosed as a thyroid nodule by US.